Il ruolo centrale della Chiesa cattolica nell’amministrazione delle leggi razziali: il caso di Bologna - Kertzer, David I. (Annali di storia dell' esegesi, 2024)
The article presents some examples of the role of the Vatican and, more generally, the degree of involvement of the Italian Catholic Church in the administration of the racial laws in Italy. In this anti-Jewish action, the cooperation between the Fascist state and the Catholic Church was generally characterized by friendly relations. The operation of the racial laws depended on the Church providing the state with documentation that would enable it to decide whether an individual was to be judged as belonging to the Jewish or Aryan race. This certainly did not mean that there were no tensions between the Fascist state and the Vatican in this area, especially in cases where the individual was considered Catholic by the Church but Jewish by the state. In fact, the Vatican never ceased to pressure the Fascist government to consider all converts (regardless of the date of conversion) as belonging to the Aryan race, a pressure that Mussolini steadfastly resisted until the end.